Improving History Learning Outcomes for Class VII B Students at SMP Negeri 3 Trucuk, Klaten Through the Role Playing Learning Model in 2012/2013 - Prihantoro, Fendy Yon (Indonesian Journal of History Education, 2017)
This study aimed to determine whether the role-playing learning model improves the learning outcomes of students of class VII B in SMP Negeri 3 Trucuk, Klaten, academic year 2012/2013. The approach used in this study is action research. Working procedures in this classroom action research consist of four main components: planning, implementation, observation, and reflection. The subjects were students of class VII B, amounting to 34 students with data analysis using descriptive analysis percentage. Learning outcomes in the second cycle have increased; it can be seen from the average value of 73.13, which increased by 4.24% from the average value of the first cycle, which is equal to 70.15. classical completeness percentage also increased from 69.69% in the first cycle to 90.9% with an increase of 30.43%.